Iron overload triggers redox-sensitive signals in human IMR-32 neuroblastoma cells - Salvador, Gabriela Alejandra (2011)
Excessive neuronal iron has been proposed to contribute to the pathology of several neurodegenerative diseases including Alzheimer´s and Parkinson´s diseases. This work characterized human neuroblastoma IMR-32 cells exposure to ferric ammonium citrate (FAC) as a model of neuronal iron overload and neurodegeneration. The consequences of FAC treatment on neuronal oxidative stress and on the modulation of the oxidant-sensitive transcription factors AP-1 and NF-êB were investigated. Incubation with FAC (150ìM) resulted in a time (3-72h)-dependent increase in cellular iron content, and was associated with cell oxidant increase. FAC caused a time-dependent (3-48h) increase in nuclear AP-1- and NF-êB-DNA binding. This was associated with the upstream activation of the mitogen activated kinases ERK1/2, p38 and JNK and of IêBá phosphorylation and degradation. After 72h incubation with FAC, cell viability was 40% lower than in controls. Iron overload caused apoptotic cell death. After 48-72h of incubation with FAC, caspase 3 activity was increased, and chromatin condensation and nuclear fragmentation were observed. In summary, the exposure of IMR-32 cells to FAC is associated with increased oxidant cell levels, activation of redox-sensitive signals, and apoptosis.